(untitled) (International Journal of Engineering and Computer Science, 2014)
A gesture recognition system is such a system that recognizes and differentiates between ‘gestures’. These gestures can be any type of facial or body gestures. Various facial expressions constitute facial gestures. Similarly the various gestures that can be made using our hand, or the palm to be more specific are called ‘HAND GESTURES’ In this project, we aim to develop such a system that is able to recognize some of such ‘hand gestures’ and differentiate between them, thus triggering a certain event corresponding to the gesture. We propose to develop a system that can successfully recognize hand into two dimensional hand gestures, using an IR sensor matrix for the purpose of recognition. We also plan to connect the recognition system to a computer keyboard emulation system so that appropriate gestures can cause corresponding keyboard events like pressing and releasing of a key. we reduce the number of the required IR sensors to two and thus reduce the power consumption, which is mentioned as a critical issue in Even using the limited information from only two IR sensors, our system can achieve accurate gesture recognition using the proposed IR feature set and the classifier.